Democratic politics as interpretation of time - Mongardini, Carlo (1996)
Abstract: "Modern culture has found in representative democracy the most refined form of government of our time. This form of democracy created and increments public time as confrontation of political parties, of ideologies, of opinions and at the same time as occasion of political participation. The emergence of economic time and of economistic mentality has led to a radical ideological transformation of the meaning of contemporary politics. Public time, within which democratic dialectic took place, has become publicity time; the moral tie of citizenship has been substituted by a plurality of demands; the representation has been reduced to a representation of vested interests, namely a debased form of representation limited in time, space and function. In face of radical changes and of the claims of economistic mentality one could argue that the political time has come to an end and that the future will be decided by economic time and the force of vested interest. But it is also possible th